NO and ABA Interaction Regulates Tuber Dormancy and Sprouting in Potato - Wang, Zhike; Ma, Rui; Zhao, Mengshi; Wang, Fangfang; Zhang, Ning; Si, Huanjun (Frontiers in Plant Science, 2020)
In plants, nitric oxide synthase (NOS)-like or nitrate reductase (NR) produces nitric oxide (NO), which is involved in releasing seed dormancy. However, its mechanism of effect in potato remains unclear. In this study, spraying 40 μM sodium nitroprusside (SNP), an exogenous NO donor, quickly broke tuber dormancy and efficiently promoted tuber sprouting, whereas 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (c-PTIO), an NO scavenger, repressed the influence of NO on tuber sprouting. Compared with the control (distilled water), SNP treatment led to a rapid increase in NO content after 6 h and a decreased abscisic acid (ABA) content at 12 and 24 h. c-PTIO treatment significantly inhibited increase of NO levels and increased ABA production. In addition, NG-nitro-L-arginine methyl ester, an NOS inhibitor, clearly inhibited the NOS-like activity, whereas tungstate, an NR inhibitor, inhibited the NR activity. Furthermore, NO promoted the expression of a gene involved in ABA catabolism (StCYP707A1, encoding ABA 8′-hydroxylase) and inhibited the expression of a gene involved in ABA biosynthesis (StNCED1, encoding 9-cis-epoxycarotenoid dioxygenase), thereby decreasing the ABA content, disrupting the balance between ABA and gibberellin acid (GA), and ultimately inducing dormancy release and tuber sprouting. The results demonstrated that NOS-like or NR-generated NO controlled potato tuber dormancy release and sprouting via ABA metabolism and signaling in tuber buds.